MODEL IMPLEMENTASI P5 MELALUI KARYA SENI TARI DENGAN JUDUL “TARI GEMARIPAH AREK SUROBOYO” SEBAGAI MEDIA MENUMBUHKAN MINAT BAKAT DI SDN DUPAK 1 SURABAYA - Nugroho, Kukuh Budi; Kaliwanovia, Tasiawati Salsa (JS (JURNAL SEKOLAH), 2024)
Abstract: The era of massive globalization is increasingly having an impact on learning loss or loss of learning due to lagging behind which is the impact of the Covid-19 pandemic. Responding to these problems, the Ministry of Education, Culture, Research and Technology launched the Independent Curriculum with an emphasis on learning on a project basis to support the creation of the Pancasila Student Profile character. This research aims to find out how to implement P5 through a dance work entitled "Gemaripah Arek Suroboyo Dance" in cultivating student interest and talent at SDN Dupak 1 Surabaya. This type of research is included in research with a descriptive qualitative approach using observation and interview methods. Based on the implementation of P5 through the art work "Gemaripah Arek Suroboyo Dance", it can be concluded that students' interest in learning is more stimulated by holding project-based learning, performances and regular practice of this work of art. Apart from that, "Gemaripah Arek Suroboyo Dance" also fosters and attracts students' interest in learning the art of dance in more depth. Contribution and participation, such as the presence of students, contributing to ideas in preparation for the art performance, and the students' consistency in practicing, succeeded in encouraging the students' talents in dance works Keyword: P5, Interest Talent, Dance Art Abstrak: Era globalisasi yang masif semakin memberikan dampak terhadap learning loss atau hilangnya pembelajaran akibat ketertinggalan yang merupakan dampak dari masa pandemi Covid-19. Menyikapi permasalahan tersebut, Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi meluncurkan Kurikulum Merdeka dengan penekanan pembelajaran pada basis proyek untuk mendukung terciptanya karakter Profil Pelajar Pancasila. Penelitian ini bertujuan untuk mengetahui bagaimana implementasikan P5 melalui karya seni tari dengan judul “Tari Gemaripah Arek Suroboyo” dalam menumbuhkan minat dan bakat siswa di SDN Dupak 1 Surabaya. Jenis penelitian ini masuk ke dalam penelitian dengan pendekatan kualitatif deskriptif dengan metode observasi dan wawancara. Berdasarkan implementasi P5 melalui karya seni "Tari Gemaripah Arek Suroboyo", dapat disimpulkan bahwa minat para siswa untuk belajar lebih terpacu dengan diadakannya pembelajaran berbasis proyek pementasan serta latihan rutin dari karya seni ini. Selain itu, "Tari Gemaripah Arek Suroboyo" turut menumbuhkan dan menarik minat para siswa untuk belajar seni tari lebih mendalam. Kontribusi serta partisipasi seperti kehadiran siswa, turut menuangkan ide dalam persiapan pentas seni, hingga konsistensi para siswa untuk berlatih, berhasil mendorong bakat para siswa dalam karya seni tariKata Kunci: P5, Minat Bakat, Seni Tari